Research on the Impact of Management Shareholding Ratio on Corporate Innovation: Based on the Mediating Effect of Financial Deepening - Quan, Peng; Chen, MingJing; Tan, ZhongZhuoFei (LP3kM Buddhi Dharma University, 2024)
The management shareholding ratio is an indicator to measure the degree of separation between ownership and management in a company. The lower the management shareholding ratio, the higher the degree of separation between ownership and management. Research and development innovation is the key to measuring the development of a company. The ratio of management shareholding ratio will affect the level of innovation in the company. Financial deepening refers to non-financial enterprises whose profits come more from investment activities. Therefore, this study used data from China from 2014 to 2018 to research the impact of management shareholding ratio on innovation R&D investment and output in non-financial enterprises through a fixed effects model. The degree of financial deepening is added as an intermediary variable to investigate the effect of management shareholding ratio on enterprise innovation under the influence of financial deepening. Ultimately, it was found that management shareholding ratio weakens the degree of financial deepening in enterprises, thereby promoting innovation R&D investment and output.